Analysis of the Saluni Santri Dictionary from Dr. Ali Al-Qasimy’s Perspective - Tsabit, Imaduddin Said; Hikmah, Khizanatul (STIQ Amuntai, 2024)
The existence of the components of dictionary preparation that have been proposed by experts in the field can be used as a benchmark in assessing the ideal dictionary. This research aims to analyze the existence of the components in the Santri Saluni Dictionary by using Dr. Ali Al-Qasimy's perspective. The method used in this research is library research with descriptive characteristics. The results of the study found that the Santri Saluni Dictionary meets 16 of the 25 components proposed by Dr. Ali Al-Qasimy. These components are: a.) the initial part: the purpose of preparing the dictionary, the sources used, the background of the preparation, instructions for using the dictionary, grammar guidelines, the amount of material in the dictionary, the meaning of symbols, and also other information in the form of print and publisher info, and table of contents, b.) the main part: the font used, the column model, phonetic information, morphological information, semantic information, and examples of word usage, c.) the final part: table components, bibliography and brief information about the dictionary on the back cover.